2021
DOI: 10.1038/s41396-021-01053-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal niche differentiation among closely related marine bacteria

Abstract: Bacteria display dynamic abundance fluctuations over time in marine environments, where they play key biogeochemical roles. Here, we characterized the seasonal dynamics of marine bacteria in a coastal oligotrophic time series station, tested how similar the temporal niche of closely related taxa is, and what are the environmental parameters modulating their seasonal abundance patterns. We further explored how conserved the niche is at higher taxonomic levels. The community presented recurrent patterns of seaso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 75 publications
14
59
0
Order By: Relevance
“…The recurrent shifts in microbial structure and activity followed typical seasonal patterns. Physical mixing of the water column in early winter seemed to be responsible for a “resetting” of the microbial ecosystem from a low diversity state in summer, when the microbial community in the EMS is nutrient depleted ( Thingstad et al, 2005 ; Tanaka et al, 2011 ; Ben Ezra et al, 2021 ), to a high diversity state in winter, as previously proposed for the Northwestern Mediterranean Sea ( Salter et al, 2015 ; Auladell et al, 2021 ). Our two early winter cruises showed differences in some environmental parameters such as temperature and fluorescence ( Supplementary Table S5 ) pointing to different mixing conditions.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The recurrent shifts in microbial structure and activity followed typical seasonal patterns. Physical mixing of the water column in early winter seemed to be responsible for a “resetting” of the microbial ecosystem from a low diversity state in summer, when the microbial community in the EMS is nutrient depleted ( Thingstad et al, 2005 ; Tanaka et al, 2011 ; Ben Ezra et al, 2021 ), to a high diversity state in winter, as previously proposed for the Northwestern Mediterranean Sea ( Salter et al, 2015 ; Auladell et al, 2021 ). Our two early winter cruises showed differences in some environmental parameters such as temperature and fluorescence ( Supplementary Table S5 ) pointing to different mixing conditions.…”
Section: Discussionmentioning
confidence: 52%
“…The observed abundance of the dominant group, SAR11, throughout the year is consistent with data reported for oligotrophic ocean gyres ( Carlson et al, 2009 ; Eiler et al, 2009 ; Morris et al, 2012 ; West et al, 2016 ) though high SAR11 abundances have also been reported from surface waters of offshore stations in the oligotrophic Southern Adriatic Sea ( Korlević et al, 2015 ; see Supplementary Table S9 for a comparison of Mediterranean and open ocean abundances). SAR11 relative abundances at our most coastal station 1 were higher (36%–42% of DNA reads in spring and summer) than those found at coastal stations in other parts of the Mediterranean Sea, including the Northwestern Mediterranean, Southern Mediterranean, and the Adriatic Sea ( Alonso-Sáez et al, 2007 ; Tinta et al, 2015 ; Quéméneur et al, 2020 ; Auladell et al, 2021 ; see Supplementary Table S9 ), highlighting the overall more oligotrophic status of the South Eastern Levantine basin even close to the coast.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The core microbiome of our model system comprises Alphaproteobacteria, Bacteroidia, Gammaproteobacteria, and Cyanobacteria as previously reported for coastal marine ecosystems ( Lindh et al, 2015 ; Maresca et al, 2018 ; Pearman et al, 2018 ; Ruiz-González et al, 2019 ; Adyasari et al, 2020 ) and also the Northern Adriatic ( Celussi and Cataletto, 2007 ; Šilović et al, 2012 ; Tinta et al, 2015 ; Paliaga et al, 2017 ; Buccheri et al, 2019 ). Our model ecosystem is strongly subjected to seasonal variations in seawater temperature, solar radiation, weather patterns (winds, freshwater inputs), changes in nutrient availability, stratification, etc., which were recognized as important forcing factors driving seasonal variations in bacterial community structure and function ( Gilbert et al, 2012 ; Fuhrman et al, 2015 ; Auladell et al, 2021 ). Therefore, we conducted in situ surveys in different seasons to be able to distinguish between variations of microbial communities triggered by seasonal variations of abiotic and biotic conditions and those caused by different distance from pollution sources.…”
Section: Discussionmentioning
confidence: 99%